2009
DOI: 10.1111/j.1472-8206.2009.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of P2Y receptors in pyridoxal‐5′‐phosphate‐induced cardiac preconditioning

Abstract: Using an isolated non‐working rat heart model, this study investigated the mechanisms of pharmacological pre‐conditioning (PC) induced by P2Y receptor stimulation with pyridoxal‐5′‐phosphate (PLP). After 6‐hydroxydopamine pretreatment and a 15‐min stabilization period, isolated rat hearts were perfused for 25 min then subjected to 40 min of global ischemia and 30 min of reperfusion (I/R); exposed for 15 min to 0.05 μm PLP bracketed for 25 min with broad‐spectrum P2 antagonists (suramin or PPADS) or with more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
4
12
0
Order By: Relevance
“…However, the ATP-induced increases in [Ca 2ϩ ] i were almost completely abolished in cells incubated in Px, indicating that Px is a viable P2 receptor antagonist in murine neuronal cells. This finding is consistent with similar studies in both neuronal cells and in isolated cardiomyocytes (29,43,60), but to our knowledge, this novel finding is the first demonstration in isolated DRG neurons, which are of particular relevance to the EPR.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, the ATP-induced increases in [Ca 2ϩ ] i were almost completely abolished in cells incubated in Px, indicating that Px is a viable P2 receptor antagonist in murine neuronal cells. This finding is consistent with similar studies in both neuronal cells and in isolated cardiomyocytes (29,43,60), but to our knowledge, this novel finding is the first demonstration in isolated DRG neurons, which are of particular relevance to the EPR.…”
Section: Discussionsupporting
confidence: 82%
“…Nonetheless, localized IV infusion of Px into the forearm increased systemic plasma PLP levels ϳ2-fold (see RESULTS), consistent with the increases noted in the available human literature (9). In rats, perfusion of isolated hearts with 0.05 M PLP (i.e., 50 nM) effectively blocks P2 receptors (43). After Px infusion in the current study, plasma PLP was ϳ200 nM, which is sufficient to antagonize P2 receptors.…”
Section: In Vivo Human Protocolsupporting
confidence: 74%
See 1 more Smart Citation
“…Thus, it was proposed that ATP-loaded liposomes could be developed as a treatment for myocardial ischaemia [598]. It has been suggested that P2Y6R and P2Y11R are involved in pyridoxal-5′-phosphate-induced cardiac pre-conditioning in rat hearts [599]. ADP acting on endothelial P2Y1R plays a major role in coronary flow during post-ischaemic hyperaemia [600].…”
Section: Ischaemiamentioning
confidence: 99%
“…Recent research suggests that at least part of the protective effect observed during reperfusion by PLP may be mediated through its inhibitory action on purinergic receptors. The possible receptors expressed in cardiomyocytes and subject to inhibition by PLP are P2Y1, P2Y2, P2Y4, P2Y6, and P2Y11 subtypes [53]. Taking together, the strategy of cell therapy following a heart attack could base on activation of P2Y14 purinergic receptors expressed by bone marrow stem cells which then would induce migration to the site of injury and thus could restore heart tissue before the formation of a scar.…”
Section: Heart Injurymentioning
confidence: 99%